2008
DOI: 10.1897/07-273.1
|View full text |Cite
|
Sign up to set email alerts
|

Chronic exposure to low concentrations of waterborne cadmium during embryonic and larval development results in the long‐term hindrance of antipredator behavior in zebrafish

Abstract: Abstract-Cadmium has been recognized for some time as a potent environmental pollutant with the capability of disrupting olfactory-mediated behaviors. Failing to respond to chemical cues in the environment could adversely affect foraging, reproduction and predator avoidance. Recognizing this impaired perception as a serious ecological problem has been undermined by the fact that the damage is often reversible; short depuration periods of 5 d may allow for the re-establishment of responses to chemical cues. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 33 publications
2
25
0
Order By: Relevance
“…Other investigators have shown that a brief Cd exposure (3 h) at 80 hpf leads to long-term behavioral deficits in the juvenile zebrafish as measured by decreased alarm responses (Blechinger et al, 2007). Similarly, embryonic zebrafish exposed to 20 μg·L −1 Cd for 50 days did not respond to alarm cues even after a 2 week depuration, suggesting a disruption of olfactory neurogenesis (Kusch et al, 2008). In the present study, olfactory cell death and disruption of the olfactory sensory epithelium were observed under short-term exposure to 25 μM Cd (2810 μg·L −1 Cd) in larvae, supporting the hypothesis that cell death and the disruption of olfactory sensory cells are mechanisms of Cd-induced olfactory impairment .…”
Section: Discussionmentioning
confidence: 95%
“…Other investigators have shown that a brief Cd exposure (3 h) at 80 hpf leads to long-term behavioral deficits in the juvenile zebrafish as measured by decreased alarm responses (Blechinger et al, 2007). Similarly, embryonic zebrafish exposed to 20 μg·L −1 Cd for 50 days did not respond to alarm cues even after a 2 week depuration, suggesting a disruption of olfactory neurogenesis (Kusch et al, 2008). In the present study, olfactory cell death and disruption of the olfactory sensory epithelium were observed under short-term exposure to 25 μM Cd (2810 μg·L −1 Cd) in larvae, supporting the hypothesis that cell death and the disruption of olfactory sensory cells are mechanisms of Cd-induced olfactory impairment .…”
Section: Discussionmentioning
confidence: 95%
“…Exposing fish to a toxicant before exposure to an alarm cue can lead to information about the olfactory-mediated behavioural effects of this substance. It was shown for example that chronic exposure to low concentrations of cadmium during development results in long-term impairment of alarm responses in zebrafish (Kusch et al, 2008;Matz and Krone, 2007).…”
Section: Olfactory Toxicitymentioning
confidence: 99%
“…Heavy metal pollutants for which these effects have been shown include Cu (Carreau and Pyle 2005;Pyle and Mirza 2007), Cd (Honda et al 2008;Kusch et al 2008), and Hg (Smith and Weiss 1997). Some studies have taken these investigations into the field to show that fish in metal-contaminated lakes respond differently from fish in uncontaminated lakes.…”
Section: Heavy Metals In Aquatic Communitiesmentioning
confidence: 99%